A Scrutiny onThe Factors Affecting the Participation of Women Doing Sports and Not Doing sports in Sportive Events - Kadir Pepe; Ali Osman Kıvrak; Barbaros Serdar Erdoğan; Şirin Pepe (Türk Spor ve Egzersiz Dergisi)
The study has been conducted in order to scrutinize the factors affecting the participation of women doing sports and not doing sports in sportive events.